Grace Under Pressure: Resilience, Burnout, and Wellbeing in Frontline Workers in the United Kingdom and Republic of Ireland During the SARS-CoV-2 Pandemic - Sumner, Rachel C.; Kinsella, Elaine L. (Frontiers in Psychology, 2021)
The coronavirus pandemic has necessitated extraordinary human resilience in order to preserve and prolong life and social order. Risks to health and even life are being confronted by workers in health and social care, as well as those in roles previously never defined as “frontline”, such as individuals working in community supply chain sectors. The strategy adopted by the UK government in facing the challenges of the pandemic was markedly different from other countries. The present study set out to examine what variables were associated with resilience, burnout, and wellbeing in all sectors of frontline workers, and whether or not these differed between the UK and Ireland. Individuals were eligible if they were a frontline worker (in health and social care, community supply chain, or other emergency services) in the UK or Republic of Ireland during the pandemic. Part of a larger, longitudinal study, the participants completed an online survey to assess various aspects of their daily and working lives, along with their attitudes towards their government’s handling of the crisis, and measurement of psychological variables associated with heroism (altruism, meaning in life, and resilient coping). A total of 1305 participants (N=869, 66.6% from the UK) provided sufficient data for analysis. UK-based workers reported lower wellbeing than the Ireland-based participants. In multivariate models, both psychological and pandemic-related variables were associated with levels of resilience, burnout, and wellbeing in these workers, and these differed by country. Personal factors on the whole did not differ in their contributions to outcomes between the subgroups of workers in each country. The judgment of lower timeliness in their government’s response to the pandemic appeared to be a key driver of each outcome for the UK-based frontline workers. These findings provide initial evidence that the different strategies adopted by each country may have impacted the overall wellbeing of frontline workers, with higher detriment observed in the UK. The judgment of the relatively slow response of the UK government to their pandemic measures appears to be associated with impaired resilience, higher burnout, and lower wellbeing in frontline workers in the UK.